2010
DOI: 10.1271/bbb.100287
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt ContainingLactobacillus gasseriOLL 2716 (LG21 yogurt) Accelerated the Healing of Acetic Acid-Induced Gastric Ulcer in Rats

Abstract: We have reported that LG21 yogurt containing Lactobacillus gasseri OLL 2716 (LG21 yogurt) inhibits the formation of HCl-induced acute gastric lesions through the generation of prostaglandin E 2 . This study aimed to determine the role of viable Lactobacillus in the healing of acetic acid-induced chronic gastric ulcer.LG21 yogurt or -ray radiated LG21 yogurt was administered orally twice a day for 10 d at a dose of 5 ml/kg. LG21 yogurt significantly accelerated the healing of the ulcer, but -ray radiated LG21 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 15 publications
7
33
0
Order By: Relevance
“…Curiously, one study [28] demonstrated that bacterial colonization occurs rapidly after ulcer induction and in particular, colonization of certain bacteria including Lactobacillus could significantly improves gastric ulcer healing. Other studies have shown that probiotic bacteria Lactobacillus species, Saccharomyces boulardii , Escherichia coli strain Nissle 1917 are effective in preventing and treating acute gastric damage associated with acetic acid [12], stress [13], aspirin [29], ethanol [30], ibuprofen [31] and indomethacin [32] induced gastric ulcers. In humans, circumstantial evidence suggests that regular ingestion of a Lactobacillus -containing product protects the integrity of the gastric mucosal barrier against indomethacin [32], while others [15] have reported that the effect of using probiotic bacteria along with triple therapy is no better than using triple therapy alone for treatment of gastric ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curiously, one study [28] demonstrated that bacterial colonization occurs rapidly after ulcer induction and in particular, colonization of certain bacteria including Lactobacillus could significantly improves gastric ulcer healing. Other studies have shown that probiotic bacteria Lactobacillus species, Saccharomyces boulardii , Escherichia coli strain Nissle 1917 are effective in preventing and treating acute gastric damage associated with acetic acid [12], stress [13], aspirin [29], ethanol [30], ibuprofen [31] and indomethacin [32] induced gastric ulcers. In humans, circumstantial evidence suggests that regular ingestion of a Lactobacillus -containing product protects the integrity of the gastric mucosal barrier against indomethacin [32], while others [15] have reported that the effect of using probiotic bacteria along with triple therapy is no better than using triple therapy alone for treatment of gastric ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…As VSL#3 was administered as a live cell suspension, this formulation could have exerted its protective effects as live microbes, by their metabolites, cell wall components and/or DNA content or all of the above. We have not performed an experiment to compare the effect of live microbes and heat inactivated probiotic mixture to assess this question even though previous studies have shown that heat-killed or radiation inactivated probiotic bacteria (in a dose similar to that of live microbes) failed to promote ulcer-healing [11], [12]. Further, since we did not assessed angiogenesis, the inference that VSL#3 is promoting gastric ulcer healing through angiogenesis is only speculated based on VSL#3 ability to induce a robust up regulation of VEGF, which is critically important in angiogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated the anti-allergic effects of fermented food products such as yogurt, cheese, and soybean paste on a variety of allergic reactions, diabetes and some cancers [28-30]. Fermentation can transmute the chemical structure of some constituents to create new substances.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, the probiotic mixture VSL#3 (including Lactobacilli, Bifidobacteria and Streptococcus species) healed acetic acid induced GU in rats by increasing the expression and production of angiogenesis promoting growth factors, primarily vascular endothelial growth factor [25]. And Lactobacillus gasseri OLL 2716 could accelerate the healing of GU, which significantly influenced gastric erosive lesions and enhanced the generation of gastric mucosal prostaglandin E2 [26]. Similar to our results, after H. pylori eradication, Lactobacillus acidophilus were recolonized in the antrum and corpus.…”
Section: Discussionmentioning
confidence: 74%